Static strength evaluation of pipelines sections with crack-like defects in the weld zone - Banakhevych, Yu. V.; Banakhevych, R. Yu.; Dragilev, V. V.; Kychma, А. О. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2014)
The article propounds the evaluation method of further life time of long-term used pipelines based on the definition of their safety coefficients with regard to the changes in geometry of crack-like defects and relaxed residual stresses. There are examined welding joints of pipe sections with the existing chisel-shaped defects that are modeled by external axial surface cracks. On the basis of the two-parametric criteria of ductile-brittle failure mechanics there are set criteria ratios of evaluation of their static strength. There are obtained closed formulas for calculating safety coefficients of pipeline sections with cracks in welded joints considering variables along the pipe and beyond its residual stresses thickness. During the research we defined the residual stresses and their values averaged over the crack surface for specific pipeline sections with the external axial surface crack in the welded joint, calculated the stress intensity factor and informational stress σ ref , which characterized the mechanism of ductile failure (plastic instability), and identified on this basis the safety coefficients. There are estimated the residual stresses influence on the static strength of pipeline section with the surface cracks in the weld and, according to regulatory documents, established categorization of their danger. There is made a research of the effect of thermoplastic deformation changes of pipe length and thickness on the level and distribution of residual stresses in the areas of circular weld zones of the pipe. The article analyzes the change of safety coefficient for different dimension ratios of external axial crack, placed in the weld. The research of the actual conditions of pipelines operation, early recognition of actual sizes of chisel-shaped defects and calculation of safety coefficients of the MP sections with damages in accordance with the mentioned methodology allows experts of the production department to choose the technology and tools for the repair-and-renewal operations beforehand, taking into account the mode of transportation and supply of oil and gas to consumers, minimizing the potential risks of accidents.